PENGARUH MODEL KOOPERATIF BERBANTUAN MEDIA FLIPBOOK TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 3 MATERI BAKTERI - Amiyanti, Resti; Ningsih, Kurnia; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to identifying the effect of cooperative learning model with Flipbook to the student learning outcomes to tenth grade students of SMAN 3 Bengkayang on bacterial subject. This research form was quasy experimental design with nonequivalent control group design. The sampling technique used a saturated sample, with X IPA 2 as the experimental class and X IPA 1 as the control class. The instrument was a multiple choice test of 20 questions. The average outcome of the experimental class was 14.26 and the control class was 11.94 . Based on U Mann-Whitney test results, obtain Zcount < -Ztabel (-2.94 < -1.96), that’s mean there was a significant differences between the learning outcome using cooperative learning models with flipbook and conventional models. The value of effect size obtained in this research was 0.61 which could be  medium category. It shows us that cooperative learning model with Flipbook has an effect as much as  22.91% towards students outcomes, especially in the material of bacterial tenth grade students. Keyword : Cooperative, Flipbook, Learning outcome